2013
DOI: 10.1007/978-3-319-01532-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in Shaping Corporate Image: An Empirical Study of State-Owned Enterprises in China

Abstract: Corporate social responsibility (CSR) is highly valued by firms for seeking to drive corporate image. State-owned enterprises as special economic and social organizations also look forward to improving its corporate image through engaging into CSR, which is attracting more and more attention in academic and demands theoretical and empirical investigation. This study aims to examine the effects of CSR on corporate image in the SOEs of China. Based on a survey study we test the effects of six dimensions of CSR o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This is actually the process of establishing a sound CSR system. Yu and Hu [32] found that CSR has a positive impact on corporate image from six dimensions of economics, organization, employees, environment, community and products. In a listed company with the state as a shareholder, the government can conduct macroeconomic regulation, influence corporate decision-making, encourage enterprises to play a good social role, fulfill social responsibilities and complete information disclosure (Luo et al [33]).…”
Section: State-owned Share and Csrmentioning
confidence: 99%
“…This is actually the process of establishing a sound CSR system. Yu and Hu [32] found that CSR has a positive impact on corporate image from six dimensions of economics, organization, employees, environment, community and products. In a listed company with the state as a shareholder, the government can conduct macroeconomic regulation, influence corporate decision-making, encourage enterprises to play a good social role, fulfill social responsibilities and complete information disclosure (Luo et al [33]).…”
Section: State-owned Share and Csrmentioning
confidence: 99%
“…Ali, Danish & Asrar-ul-Haq, 2020;Dudenhausen, Röttger & Czeppel, 2020). According to Baba (2017); Yu and Hu (2014); Nalla (2011), CSR not only helps to build up a positive corporate image but it can also help to mitigate or even solve socioeconomic problems. Nguyen, Hoang and Luu (2020) even mention that organizations that practicing CSR not only increase corporate performance, but also have potential to gain greater benefits including developing positive shared values in the organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen, Hoang and Luu (2020) even mention that organizations that practicing CSR not only increase corporate performance, but also have potential to gain greater benefits including developing positive shared values in the organizations. Indeed, since the emergence of CSR in the early 1950s, more companies have become concerned about building up a good relationship with the community in order to improve their public image (Latapí Agudelo, Jóhannsdóttir & Davídsdóttir, 2019;Yu & Hu, 2014;Davis, 2014;Carroll, 2008). In Malaysia, CSR activities are dominated by mostly manufacturing companies, with the education sector being the main beneficiary of CSR initiatives (Ismail, Alias, & Mohd Rasdi, 2015).…”
Section: Introductionmentioning
confidence: 99%